Combination diagnosis of multi‐slice spiral computed tomography and secretary phospholipase A2‐IIa for solitary pulmonary nodules. Issue 2 (11th May 2017) - Hou, Hongjun; Xu, Zushan; Zhang, Hongsheng; Xu, Yan
Abstract : Introduction: This study was aimed to compare the diagnostic value of multi‐slice spiral computed tomography (CT) and secretary phospholipase A2‐IIa (sPLA2‐IIa) in differentiating between malignant and benign solitary pulmonary nodules (SPNs). Methods: A total of 223 patients with SPNs (91 patients with malignant SPNs and 132 patients with benign SPNs) were included from Weihai Central Hospital during October 2014 to December 2016. SPN diagnosis was confirmed in all patients using needle biopsy, surgery and bronchoscopy. The patients were managed with dynamic multi‐slice CT scans, and their sPLA2‐IIa levels were also detected. By selecting the area of interest of focus, the perfusion parameters of multi‐slice CT targeting the focus were obtained. Results: The levels of MTT, PS, BV, BF and sPLA2‐IIa significantly increased with increasing severity of SPNs ( P <.05). Notably, BV (area under the ROC curve [AUC]=0.915; 95%CI: 0.88‐0.95; sensitivity=91.21%; specificity=78.79%) showed a higher potential to discriminate patients with malignant SPNs from those with benign SPNs than did BF (AUC=0.712; 95%CI: 0.65‐0.78; sensitivity=72.50%; specificity=59.10%), PS (AUC=0.772; 95%CI: 0.71‐0.84; sensitivity=65.93%; specificity=82.58%) and MTT (AUC=0.600; 95%CI: 0.52‐0.68; sensitivity=52.75%; specificity=78.03%). Finally, the combined diagnostic value of BV and sPLA2‐IIa was quite ideal (AUC=0.947; 95%CI: 0.92‐0.97; sensitivity=85.70%; specificity=92.70%) for malignant and benign SPNs. Conclusions: The combined diagnostic value of BV and sPLA2‐IIa appeared as a desirable detection method for malignant and benign SPNs.